The availability of some of the Professional criteria of “Level One” Teachers’ performance in Basic Teaching are available- Afield Study from the Schools’ Managers point of view in Lattakia Governate - Sultan , Manal; Boroal , Somar; Msalm , Sana (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
This research aims to identify to what extent some of the Professional criteria of “Third Grade” Teachers’ performance in Basic Teaching are available from the Schools’ managers point of view in Lattakia Governate. To achieve this research, used the descriptive analytical approach, A sample was included (64) managers of Basic Teaching Schools in Lattakia Governorate for the academic year 2017/2018. A questionnaire was designed for Professional Standards, it contained five basic Standards which are: (preparation of lesson plans which are necessary to the learning process, the ability of educational knowledge in teacher’s specialization field, showing the distinct educational culture at teacher, the teacher’s used methods in Evaluation, classroom management), which composed of (55) Performance indicators. The research ended up with the following results: - The extent of availability some Professional criteria “Third Grade” Teachers’ performance from the View of Schools’ managers in Lattakia Governorate was middle degree. - No statistically significant differences between the averages of the Schools’ managers about the extent of availability some Professional criteria “Third Grade” Teachers’ performance from the View of Schools’ managers according to the variables (kind, years of experience), while statistically significant differences according to the variable scientific qualification in favor of postgraduate students (Master, Doctorate). The research had some suggestions, training course for Basic Teaching before joining in Teaching profession.